The impact artificial sub-surface drainage on greenhouse gas emissions, change in soil carbon storage and nutrient losses from grassland - VALBUENA PARRALEJO, NURIA (Trinity College Dublin. School of Natural Sciences. Discipline of Botany, 2019)
Irish dairy production sector has started an expansion process while achieving a 20% reduction in the National greenhouse gas (GHG) emissions and fulfilling the Water Framework Directive. Moreover, the 30% of Irish dairy farms are located on poorly permeable soils. Mole and gravel mole drainage are widely implemented as a management technique in order to improve soil permeability, maximize grass utilization and ultimately increase milk production on dairy farms. Hence, assessing the environmental impact of such systems becomes a requirement to reach the above targets. This study carried out detailed soil GHG flux and soil phosphorus (P) and nitrogen (N) losses to water measurements on a pasture-based livestock production system. This study also allowed for a much more holistic view of soil N and carbon cycle after subsurface artificial drainage implementation compared to most previous studies which have primarily focused on soil nutrients losses to water. Encompassed in this holistic study was a study of the impact of weather variability on the soil GHG emissions. The experiments were carried out on a perennial ryegrass (Lolium perenne L.)/white clover (Trifolium repens L.; 18.2%) based at Solohead Research Farm (52° 51’ N, 08° 21’ W), on a gently sloping (1.4%) site (2.5 ha) bounded by the river Pope. Four treatments (plot size: 100 x 15 m) were arranged in a randomised complete block design replicated four times were: (i) un-drained, (ii) mole drainage 1, (iii) mole drainage 2 and (iv) gravel mole drainage. Representative grab water samples associated with flow measurements were taken, filtered and analysed for P and N (from 31 March 2014 until 31 March 2015). Soil nitrous oxide (N2O), soil root respiration (CO2) and soil methane (CH4) fluxes were measured in two experiments conducted over a 36 month period. These measurements were combined with measurements of soil watertable depth (WTD), soil water filled pore space (WFPS), soil temperature, soil mineral nitrogen (N), herbage N uptake, soil organic carbon (SOC) and soil total N (TN), that were measured on a weekly and seasonal basis. The data collected over the sampling period was used to calibrate and validate the DNDC ecosystem process model in order to assess the effect of each drainage treatment on soil GHG. Historical weather (1986-2013) was used to generate 27 weather scenarios. The effects of weather variability on the soil GHG emissions were analysed and also key drivers of soil GHG fluxes were identified. Results showed drainage treatments (P<0.05) deepened the WTD and decreased WFPS. However no (P>0.05) impact of drainage treatment was detected on the soil GHG flux, soil mineral N, herbage N uptake, SOC and TN. Drainage increased the extent of dissolved inorganic N losses in the subsurface pathways. However, total P losses were lowered reduced by on avenged (114 g ha-1 year-1) by improving soil permeability and enhancing soil P sorption. Modelling results showed that gravel mole drainage can significantly lower the annual cumulative soil N2O emissions and that increased annual rainfall and mean air temperature can significantly increase soil cumulative N2O emissions under drained and un-drained soils. The clay-loamy soils with high soil organic carbon and moist maritime climate at this site contained conditions that enhanced the sorption of the P dissolved in the water percolating through the soil drainage system. Moreover, it also contained conditions for denitrification, which may explain the lack of differences between treatments in the cumulative soil N2O flux between drained and undrained treatment and relatively low N losses to ground water in the present study. Although modelling results showed that drainage treatment can significantly lower the overall soil N2O emissions, the accounted difference was 0.3 ±0.07 kg N2O-N ha-1 year-1. Further analysis also showed that years with greater rainfall and mean air temperature increased the soil N2O-N emissions, with no significant difference between soil cumulative N2O emissions from drained and undrained treatments. This study highlights that mole and gravel mole drainage techniques for improving trafficability and grass utilization did not have a major impact the eutrophication of water bodies and on the extent of soil GHG emissions under the management and conditions described in the present study. It also shows the complexity underlying the soil GHG emissions and particularly soil N2O flux. And the strong influence of weather variables on the soil N and carbon cycles. As weather cannot be controlled the emphasis should be made in developing management techniques for the control of the key parameters that drive soil GHG emissions and avoid favourable conditions for soil nutrient losses and soil GHG emissions.
APPROVED
Keywords: Drainage; Greenhouse gas